SOCIAL MEDIA STRATEGY TOWARDS THE DEVELOPMENT OF DIGITAL MARKETING STRATEGY IN HIGHER EDUCATION - Hariyanti, Novi Tri; Wirapraja, Alexander (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Higher education is an organization established and managed by the community by forming a legal entity that is non-profit and is required to obtain a Material permit. The problem that is often faced by private higher education institutions is the difficulty in increasing the number of new students entering the new academic year. This problem causes higher education institutions to have difficulty developing because the largest amount of income is from the number of students. This study used a descriptive qualitative method by taking samples from several private higher education institutions by conducting interviews with several marketing staff representatives from each higher education institution. The results obtained are the mapping and analysis of social media utilization strategies according to the resource capabilities of each higher education institution with reference to the marketing mix (7P), so it can be concluded that there is still a lot of potential from higher education institutions that can be exposed more widely in order to maximize their abilities to get more prospective students.